PENGEMBANGAN MANAJEMEN SARANA DAN PRASARANA SEKOLAH TERHADAP MUTU PENDIDIKAN SEKOLAH DASAR DI SIDOARJO - M. Shodiq; Maimunah, Siti (Universitas Islam Balitar, 2021)
The background of this research stems from the researcher's interest in student achievement at Sekolah Dasar Negeri 2 Pucang Sidoarjo as a quality school equipped with adequate facilities and infrastructure. Therefore, the researcher conducted research related to the development of school facilities and infrastructure management on the quality of elementary school education in Sidoarjo.This research used descriptive qualitative method, conducted with observation, documentation, and interview techniques. The researcher also used data display from the theory of Miles and Huberman, in which the data were made simply and processed in the form of words, tables, narratives, sentences, matrices, and graphs. The results of this study indicated that the facilities and infrastructure in the state elementary school in Sidoarjo have met the standards and are in very good condition, namely: a) The educational facilities and infrastructure were very good and met the standards (100%), b) The teacher room and classrooms also met the standards (98%), c) The also met the standards (99%), d) Administration Room (TU) 80%, e) The quality of school education including school accreditation grade A, national exam A, academic and non-academic achievements, namely the first winner in mathematics science competition, the first winner in taekwondo competition, and the first winner in rock climbing competition (100%). This research concludes that the development of school facilities and infrastructure management has an important role in improving the quality of educationand developing student achievement in sports, science, and technology.